Letter to the Editor: Medication-Overuse Headache is Common in Portuguese Migraineurs - Marcelo Duarte Mendonça; André Caetano; Manuel Salavisa; Miguel Viana-Baptista; Rita Miguel; Miguel Pinto; Raquel Barbosa; Filipa Ladeira; Francisca Sá; Rita Pelejão (Acta Médica Portuguesa, 2017)
N/A.